A versatile hard–soft N/S-ligand for metal coordination and cluster formation. Issue 62 (13th July 2016) - Benson, Callum G. M.; Plajer, Alex J.; García-Rodríguez, Raúl; Bond, Andrew D.; Singh, Sanjay; Gade, Lutz H.; Wright, Dominic S.
Abstract : The new ligand [S-P(μ-N t Bu)]2 2− has adaptable hard–soft character with respect to the coordinated metal centre and can be used to construct large cage architectures. Abstract : Deprotonation of the thialdiphosphazane [SPH(μ-N t Bu)]2 with a range of metal-bases gives the stable dianion [S–P(μ-N t Bu)]2 2−, which is valence-isoelectronic with the widely-used [RN-P(μ-NR)]2 2− ligand. Structural studies show that the new ligand has adaptable hard–soft character with respect to the coordinated metal centre and that its multidentate nature can be exploited to construct large cage architectures.